Electric-field-driven magnetic domain wall as a microscale magneto-optical shutter - Nikolai E. Khokhlov (Nature Portfolio, 2017)
Abstract Nowadays, spintronics considers magnetic domain walls as a kind of nanodeviсe that demands for switching much less energy in comparison to homogeneous process. We propose and demonstrate a new concept for the light control via electric field applied locally to a magnetic domain wall playing the role of nanodevice. In detail, we charged a 15-μm-thick metallic tip to generate strong non-uniform electric field in the vicinity of the domain wall in the iron garnet film. The electric field influences the domain wall due to flexomagnetoelectric effect and causes the domain wall shift. The resulting displacement of the domain wall is up to 1/3 of domain width and allows to demonstrate a novel type of the electrically controlled magneto-optical shutter. Polarized laser beam focused on the electric-field-driven domain wall was used to demonstrate the concept of a microscale Faraday modulator. We obtained different regimes of the light modulation – linear, nonlinear and tri-stable – for the same domain wall with corresponding controllable displacement features. Such variability to control of domain wall’s displacement with spatial scale of about 10 μm makes the proposed concept very promising for nanophotonics and spintronics.